AGRICULTURE IN MOUNTAIN AREAS OF PODKARPACKIE VOIVODSHIP, POLAND: DEFINITION, CHARACTERISTICS, LIMITATIONS IN AGRICULTURAL PRODUCTION, DEFICITS AND DEVELOPMENT OPPORTUNITIES - Stanisław ZAJĄC; Dariusz KUSZ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Exogenous and endogenous factors influencing the condition of agriculture in mountain areas of Podkarpackie voivodeship were presented. The scope of the research includes the determination of characteristic features, limitations in agricultural production, deficits and development opportunities as well as ways of using/reinforcing existing trends in the agri-food sector in the aspect of mountain farming development in the areas of Podkarpackie voivodeship. Preservation of agricultural production in this valuable natural area is very important due to the numerous social, economic, environmental, but also cultural functions performed by agriculture and farms here. Departure of inhabitants from agriculture may cause irreversible negative phenomena resulting in reduction of landscape attractiveness and consequently tourist attractiveness. Mountain areas have development opportunities which should be utilised by coordinating actions at the regional and macro-regional level.